Trends in inpatient antibiotic use in Indonesia and the Philippines during the COVID-19 pandemic - Amara Z. Fazal; Olivia L. McGovern; Garrett W. Mahon; Fernanda C. Lessa; Maria Tarcela Gler; Jemelyn Garcia; Mark John Festin; Kuntaman Kuntaman; Ida Parwati; Cherry Siregar; Jay Christian D. Muere; Gina De Guzman Betito; et al. (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract